The Merits of Regional Cooperation: The Case of South Asia - Wolf, Siegfried O.; Casaca, Paulo; Flanagan, Anne J.; Rodrigues, Cátia (Springer International Publishing Imprint: Springer, 2014)
This book highlights various cutting-edge topics and approaches to cooperation and regional integration in South Asia. Contributions from both South Asian and EU scholars carry the distinctive flavour of differing perspectives, in order to identify possible driving factors for regional cooperation. The book is divided into four parts: Peace and Stability focuses on how to combat terrorism and ideologies of hate, looks at governance in the context of cultural diversity, and examines the role of education in achieving traditional and human security; Economic Cooperation deals with potential EU-India trade relations as well as the issue of how to transform the South Asian Association for Regional Cooperation (SAARC) into an effective and coherent economic space; Efficient Use of Resources analyses how the region can achieve more development; EU-South Asia relations elaborates on potential areas of cooperation between the two regions
Description based upon print version of record
Keywords: Aufsatzsammlung; Sicherheitspolitik; Wirtschaftspolitik; South Asian Association for Regional Cooperation